(untitled) (Cadernos de Sociomuseologia, 2025)
Abstract: This article aims to present some results of the R&D Project “The place of Intangible Cultural Heritage in educational processes in Greater Lisbon”, developed within the scope of the Center for Interdisciplinary Studies in Education and Development of the Lusófona University (CeiED/ULusófona) and the Department of Museology of the same University. The aforementioned project sought to identify initiatives in the area of ​​intangible cultural heritage that encourage the appreciation of cultural diversity and citizenship in formal education spaces in curricular and extracurricular activities of schools in Greater São Paulo. It seeks to assist in a broader understanding of the concept of heritage, with a particular focus on intangible cultural heritage and possible connections with sociomuseology, in addition to reflecting on articulations between museology and education that seek social development, as well as the social function of heritage from the perspective of valuing diversity and promoting efforts to build a community dialogue for inclusion. This discussion, which was the basis of the methodology used, contributes to the analysis and understanding of cultural manifestations and processes in the educational dynamics investigated. Keywords: Heritage Education, Intangible Cultural Heritage and Sociomuseology